The history of Ilizarov. (July 2013) - Battaloglu, Emir; Bose, Deepa
This review describes the life and works of Gavril Abramovich Ilizarov. The authors attempt to explain Ilizarov's motivation and the key stages of his career which brought him to international acclaim. The article also discusses the key principles of Ilizarov's methods and how these can be clinically applied.